Making the Final Cut — Mechanisms Mediating the Abscission Step of Cytokinesis - Schiel, John A.; Prekeris, Rytis (TheScientificWorld, 2010)
Cytokinesis is the final stage of mitotic cell division that results in a physical separation of two daughter cells. Cytokinesis begins in the early stages of anaphase after the positioning of the cleavage plane and after the chromosomes segregate. This involves the recruitment and assembly of an actomyosin contractile ring, which constricts the plasma membrane and compacts midzone microtubules to form an electron-dense region, termed the midbody, located within an intracellular bridge. The resolution of this intracellular bridge, known as abscission, is the last step in cytokinesis that separates the two daughter cells. While much research has been done to delineate the mechanisms mediating actomyosin ring formation and contraction, the machinery that is responsible for abscission remains largely unclear. Recent work from several laboratories has demonstrated that dramatic changes occur in cytoskeleton and endosome dynamics, and are a prerequisite for abscission. However, the mechanistic details that regulate the final plasma membrane fusion during abscission are only beginning to emerge and are the subject of considerable controversy. Here we review recent studies within this field and discuss the proposed models of cell abscission.